Jiaweishaoyao Decoction Alleviates DSS-Induced Ulcerative Colitis via Inhibiting Inflammation - Huixia Qiao; Yahui Huang; Xiaoyan Chen; Long Yang; Yue Wang; Rongrong Xu (Gastroenterology Research and Practice)
Purpose. Jiaweishaoyao decoction (JWSYD) is a traditional prescription of Chinese medicine that is initially used for the treatment of diarrhea. This study is aimed at investigating the effects of JWSYD on DSS-induced ulcerative colitis (UC). Methods. DSS-induced UC mice and LPS-induced RAW264.7 cells were used as the UC model in vivo and in vitro. UC was assessed by body weight, disease activity index (DAI), colon length, spleen weight, and histopathological score (HE staining). The levels of TNF-α, IL-1β, and IL-6 were analyzed by ELISA and qRT-PCR. The levels of NLRP3 inflammasome- and NF-κB pathway-associated proteins were measured by western blot. Results. JWSYD alleviated DSS-induced UC in respect to body weight, DAI, colon length, spleen weight, and histopathological score. JWSYD reduced the levels of TNF-α, IL-1β, and IL-6 in DSS-induced UC mice and the supernatants of LPS-induced RAW264.7 cells. JWSYD suppressed the protein levels of inflammasome-associated proteins, including NLRP3, ASC1, Procaspase-1, Cleaved caspase-1, and Cleaved IL-1β in DSS-induced UC mice and LPS-induced RAW264.7 cells. In addition, JWSYD suppressed the NF-κB pathway in vitro and in vivo. Conclusion. JWSYD alleviated DSS-induced UC via inhibiting the NLRP3 inflammasome and NF-κB pathway.